Complex Sentence as Sign of Syntactic Complexity, Realized on Basis of Principle of Iconicity (Experience of Researching German Scientific Discourse) - T. V. Burdaeva; M. M. Khalikov (Научный диалог, 2021)
The question is considered of how, within a separate fragment of intellectual and communicative activity (using the example of modern German-language scientific and technical discourse), the mechanism for implementing the category of syntactic complexity of an utterance based on the principle of iconicity in the processes of linear-structural organization of the text is revealed. It is shown that iconicity is the property of a linguistic sign to correspond to the object it denotes or the real situation it denotes. Insufficient study of iconicity is noted both in terms of theoretical and epistemological, and in the aspect of the variety of conditions, goals and methods of implementing communicative practices. The research material is considered on the basis of a verified model of semiotic analysis in the field of syntax (O. A. Kostrova) in the aspect of discrete and combinatorial implementation of the structural-syntactic, semantic-syntactic and pragmatic-syntactic iconicity of complex sentences in scientific discourse. It has been established that this or that type of iconicity is determined by the stylistic context and the parameter of marking / unmarking. It is proved that in scientific discourse, one elementary complex sentence, characterized by unmarking, can simultaneously include signs of all three types of iconicity. At the same time, it is indicated that, reflecting the real situation, the signs of one or another type of iconicity, realized in a complex sentence, may be lost.